Appreciative Learning for Immersive Reward System in Education Game Development - Hanny Haryanto; Ardiawan Bagus Harisa; Indra Gamayanto (Bina Nusantara University, 2021)
Game replayability is very important in serious game to maximize the understanding for the learning content. The replayability is the result from the gameplay experience. Games have the advantage of providing a fun experience, and immersion is a vital element in game design to produce the experience. However, the design of immersion in games is often not well conceptualized so that it does not produce the expected experience. This study uses Appreciative Learning based reward system, which focuses on positive things such as peak achievements, opportunities, exploration of potential and optimism for the future. The reward activity consists of four stages, namely Discovery, Dream, Design and Destiny. Reward personalization is done by regulating reward behavior using artificial intelligence which runs in all four stages. Appreciative Learning will be used to design immersive experiences consisting of sensory, imaginary and challenge-based immersion, which are the three main elements of immersive games. Intelligent agent behavior is modeled using the Finite State Machine. This study produces an immersive reward design that is applied to the concept of Appreciative Learning in designing a serious game.